Development Of Multi Duty Cycle Sequential Gated Pulse Frequency Generator For Resonant Electrolysis - Gan, Leong Ming; R. A., Bakar (2010)

(untitled)
For the sustainable future, the potential energy source, transforming method, energy cost per efficiency are inter-related and the development of the future energy plant is a long term research which involve validation of theory, prototyping and etc. No doubt that hydrogen fuel is one of the potential energy carry but the harvesting of hydrogen from water is constraint by the Faraday’s law of electrolysis where the efficiency is restricted. Researched found that harvesting hydrogen fuel based on frequency method could achieve higher efficiency than the conventional method. Therefore, a specific frequency generator is proposed to study the effect of various frequency design and voltage input to the hydrogen fracturing process. The designed model is equipped with the pulse, gated pulse and sequential gated pulse features to enhance and optimize the fracturing rate. The detail design and development of the frequency generator is also discussed in the following section.